A case of chronic ankle osteomyelitis treated with bioactive glass and tibiocalcaneal fusion - Grassi, Miriam; Larghi, Marco Mattia; Brioschi, Davide; Scazzarriello, Marianatonietta; Manzotti, Alfonso (Journal of the Foot & Ankle, 2025)
Limb-salvage surgery in cases of chronic osteomyelitis poses significant challenges for orthopedic surgeons. This case report presents the first documented instance of a successful staged limb-salvage treatment for chronic ankle osteomyelitis, combining tibiocalcaneal fusion with bioactive glass (BAG). Bioactive glass S53P4 is a synthetic, biocompatible, osteoconductive bone substitute known for its bone-bonding capabilities, antibacterial and angiogenesis-promoting properties, which could be suitable for treating bone defects in infections. The subject of this case is a 68-year-old male with long-standing uncontrolled diabetes, who presented with a sevenday history of progressive left ankle arthralgia, purulent drainage in the medial aspect of the ankle, and low-grade fever. Imaging studies confirmed the diagnosis of chronic ankle osteomyelitis. The treatment involved a multidisciplinary approach including early antibiotic therapy, rigorous glycemic control, and staged surgical interventions using biomaterials. The first surgery was debridement and adequate irrigation, bone-void filling with antibiotic cemented spacer. Later targeted antibiotic therapy, after cultural examination, progressed to total contact casting and partial progressive weight-bearing. After 24 months of follow-up, with no clinical signs of infection, no gross alteration of gait pattern, and demonstrating complete bone healing, the patient was submitted to tibiocalcaneal fusion using bioactive glass. The BAG-S53P4 represents an interesting option as a bone substitute in chronic osteomyelitis with bone loss. Level of evidence IV; Therapeutic study; Case report.